Implementasi Nilai Filosofis Pancasila Dan Agama Islam Dalam Menangkal Paham Radikalisme Di Indonesia - Dwiyana Achmad Hartanto (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2017)
The research titled "Implementation of Philosophical Value of Pancasila and Islam Religion in Counteracting Radicalism in Indonesia" is motivated by the growing understanding of radicalism in Indonesia in various layers of society, which has the potential to undermine the sovereignty of the Unitary State of the Republic of Indonesia. This study aims to (1) Analyze the importance of philosophical values ​​in Pancasila and Islam, 2) To know the implementation of the philosophical value of Pancasila and Islam in preventing the idea of ​​radicalism in Indonesia. Approach method used is normative juridical approach method. The results show that it is very important to understand the philosophical values ​​in Pancasila and Islam, because with these values ​​can be a guide in running the life of society, nation and state. Implementation of philosophical value of Pancasila and Islamic religion in serve as a tool or means in counteracting the idea of ​​radicalism in Indonesia.